Fantastic genes and where to find them: molecular basis of alcohol effects in zebrafish populations - Barbosa, Thaís Agues (2021)
Alcohol (or ethanol) is a powerful psychoactive substance and its excessive consumption may lead one to develop the alcoholism. However, its known that genetic, physiological and behavioral variations influence how individuals respond to alcohol. In this sense, comparative studies among populations from a same species are useful. Thus, we evaluated the behavioral and molecular pattern in response to alcohol of zebrafish populations (Danio rerio), using different protocols and stages of development. In the first chapter, we evaluated the behavioral pattern and mRNA levels in three zebrafish populations (AB, TU, and WT) exposed to the combination of chronic (0% or 0.5%) and acute (0% or 0.5%) alcohol concentrations. We analyzed locomotor and anxiety-like behavior, and the expression of mRNA involved in neurotransmitters affected by alcohol (Th1, Ache, Gaba1, Gad1b, Tph1, Ada1, BDNF). We observed that locomotor response (mean speed and distance traveled) and associated genes (Gaba1 and Gad1b) were similar within all populations, in which there was increased behavioral response and overexpressed levels of the gene in acute the treatment. The mRNA levels of Th1 e Ache were similar in TU e WT, in which we observed increased expression. In both acute and withdrawal treatments. Regarding anxiety, both AB and TU fish presented robust response (increased distance from the bottom during withdrawal and increased levels of Tph1 and Ada1 in both acute and withdrawal treatments), while WT didn't show alterations in behavior nor in transcriptional levels. TU fish presented increased expression of BDNF during chronic and withdrawal treatments, in contrast to AB and WT populations. In the second chapter, we exposed zebrafish embryos to alcohol (0%, 0.5% or 1.0%) from the three populations, in order to simulate the fetal alcohol spectrum disorder - FASD. We evaluated behavior in three ontogenetic phases: larval, juvenile and adult. We verified, again, consistent and patter response between AB and TU fish, while WT showed no alterations. During the larval phase, both AB and WT populations exposed to embryonic alcohol exhibited increased locomotion (mean speed and distance traveled), while TU larvae showed decreased motor response. In terms of anxiety-like, we observed decreased of the behavior (time at the edge and distance of the edge) in all populations exposed to alcohol. In juvenile phase, both AB and TU remained the motor pattern from the larval phase, but they didn't present altered anxious behavior. The WT population, otherwise, showed no altered locomotion nor anxiety-like responses. During the adult stage, both AB and TU embryonically exposed to alcohol exhibited increased motor and anxious responses. On the other hand, WT fish didn't show alterations in behavioral response. In the last chapter, we tried to stablish a new protocol of voluntary search for alcohol. After induce fish to alcoholism throughout the combination of chronic (0% or 0.5%) and acute (0% or 0.5%) alcohol concentrations, we tested their preference for alcohol or water. We observed that animals preferred the water side, evidencing that perhaps the protocol wasn't sufficient to induce seeking behavior. In general terms, alcohol response depends on the exposure regimen to the drug and the genetic background contribution. For the purposes of translational studies, standard populations commonly used in laboratories offer reliable and reproducible results, thus, they should be prioritized.